2018
DOI: 10.3389/fnmol.2018.00114
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Pannexin 1 Alters Synaptic GluN2 Subunit Composition and Spatial Reversal Learning in Mice

Abstract: Long-term potentiation (LTP) and long-term depression (LTD) are two forms of synaptic plasticity that have been considered as the cellular substrate of memory formation. Although LTP has received considerable more attention, recent evidences indicate that LTD plays also important roles in the acquisition and storage of novel information in the brain. Pannexin 1 (Panx1) is a membrane protein that forms non-selective channels which have been shown to modulate the induction of hippocampal synaptic plasticity. Ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 47 publications
(93 reference statements)
2
54
0
Order By: Relevance
“…This regulation of neurites and dendritic spines connects nicely with our earlier discovery of Panx1 proteinprotein interactions (PPIs) with dendritic spine regulating proteins, such as the actin-related protein (Arp) 2/3 complex components (Wicki-Stordeur and Swayne, 2013), and the microtubule-interacting protein collapsin-response mediator protein 2 (Crmp2) (Xu et al, 2018). A role for Panx1 in regulating neuronal development and connectivity is further supported by work revealing its role in hippocampal synaptic plasticity under naïve conditions (Ardiles et al, 2014;Gajardo et al, 2018;Prochnow et al, 2012), as well as recently reported connections to intellectual disability (Shao et al, 2016) and autism spectrum disorder (ASD) (Davis et al, 2012). Moreover, Panx1 has been implicated in synaptic dysfunction in ischemia (MacVicar and Thompson, 2010;Weilinger et al, 2016;Weilinger et al, 2013) and has been suggested to be involved in CNS dysfunction associated with Alzheimer disease (Orellana et al, 2011b) and Parkinson disease (Diaz et al, 2019).…”
Section: Introductionsupporting
confidence: 60%
“…This regulation of neurites and dendritic spines connects nicely with our earlier discovery of Panx1 proteinprotein interactions (PPIs) with dendritic spine regulating proteins, such as the actin-related protein (Arp) 2/3 complex components (Wicki-Stordeur and Swayne, 2013), and the microtubule-interacting protein collapsin-response mediator protein 2 (Crmp2) (Xu et al, 2018). A role for Panx1 in regulating neuronal development and connectivity is further supported by work revealing its role in hippocampal synaptic plasticity under naïve conditions (Ardiles et al, 2014;Gajardo et al, 2018;Prochnow et al, 2012), as well as recently reported connections to intellectual disability (Shao et al, 2016) and autism spectrum disorder (ASD) (Davis et al, 2012). Moreover, Panx1 has been implicated in synaptic dysfunction in ischemia (MacVicar and Thompson, 2010;Weilinger et al, 2016;Weilinger et al, 2013) and has been suggested to be involved in CNS dysfunction associated with Alzheimer disease (Orellana et al, 2011b) and Parkinson disease (Diaz et al, 2019).…”
Section: Introductionsupporting
confidence: 60%
“…Hippocampal slices were prepared as we previously reported (Ardiles et al, 2012;Gajardo et al, 2018). Briefly, mice were deeply anesthetized with isoflurane, brains quickly removed and hippocampus sectioned in slices of 350 µm in ice-cold dissection buffer using a vibroslicer (Leica VT1200S, Leica Microsystems, Nussloch, Germany).…”
Section: Excitatory Postsynaptic Field Recordingsmentioning
confidence: 99%
“…Synaptosomes were extracted from hippocampus of 6 m.o. male mice as we previously described (Gajardo et al, 2018). Hippocampi were homogenized in ice-cold homogenization buffer [320 mM sucrose, 4 mM 4-(2-hydroxyethyl)-1piperazineethanesulfonic acid (HEPES), and 1 mM ethylene glycol-bis(β-aminoethyl ether)-N,N,N ,N -tetraacetic acid; EGTA), pH 7.4; protease and phosphatase inhibitor cocktails] using a Dounce tissue grinder.…”
Section: Synaptosomal Fractionationmentioning
confidence: 99%
“…PANX1 is broadly and highly expressed in the brain during early postnatal development (Ray et al, 2005;Vogt et al, 2005) and localized and enriched in synaptic compartments (Zoidl et al, 2007;Sanchez-Arias et al, 2019). Pharmacological and genetic disruption of PANX1 results in enhanced hippocampal LTP induction while precluding that of LTD (Prochnow et al, 2012;Ardiles et al, 2014;Gajardo et al, 2018). Given that PANX1interacting cytoskeletal regulators, collapsin response mediator protein 2 (CRMP2) and actinrelated protein 2/3 complex (ARP2/3), are known to control dendritic spine formation (Wicki-Stordeur and Swayne, 2013;Spence et al, 2016;Zhang et al, 2016;Xu et al, 2018), it was perhaps not surprising that Sanchez-Arias et al (2019) recently showed that Panx1 deletion led to the formation of larger cortical neuron network ensembles and that this was due, in part, to increased cortical neuron dendritic spine density.…”
Section: Introductionmentioning
confidence: 99%